Computational analyses of ancient pathogen DNA from herbarium samples: challenges and prospects - Yoshida, Kentaro; Sasaki, Eriko; Kamoun, Sophien (Frontiers in Plant Science, 2015)
The application of DNA sequencing technology to the study of ancient DNA has enabled the reconstruction of past epidemics from genomes of historically important plant-associated microbes. Recently, the genome sequences of the potato late blight pathogen Phytophthora infestans were analyzed from 19th century herbarium specimens. These herbarium samples originated from infected potatoes collected during and after the Irish potato famine. Herbaria have therefore great potential to help elucidate past epidemics of crops, date the emergence of pathogens, and inform about past pathogen population dynamics. DNA preservation in herbarium samples was unexpectedly good, raising the possibility of a whole new research area in plant and microbial genomics. However, the recovered DNA can be extremely fragmented resulting in specific challenges in reconstructing genome sequences. Here we review some of the challenges in computational analyses of ancient DNA from herbarium samples. We also applied the recently developed linkage method to haplotype reconstruction of diploid or polyploid genomes from fragmented ancient DNA.